Cerebral Blood Flow of the Neonatal Brain after Hypoxic–Ischemic Injury - Tierradentro-García, Luis Octavio; Saade-Lemus, Sandra; Freeman, Colbey; Kirschen, Matthew; Huang, Hao; Vossough, Arastoo; Hwang, Misun (American Journal of Perinatology, 2021)
Objective Hypoxic–ischemic encephalopathy (HIE) in infants can have long-term adverse neurodevelopmental effects and markedly reduce quality of life. Both the initial hypoperfusion and the subsequent rapid reperfusion can cause deleterious effects in brain tissue. Cerebral blood flow (CBF) assessment in newborns with HIE can help detect abnormalities in brain perfusion to guide therapy and prognosticate patient outcomes.Study Design The review will provide an overview of the pathophysiological implications of CBF derangements in neonatal HIE, current and emerging techniques for CBF quantification, and the potential to utilize CBF as a physiologic target in managing neonates with acute HIE.Conclusion The alterations of CBF in infants during hypoxia-ischemia have been studied by using different neuroimaging techniques, including nitrous oxide and xenon clearance, transcranial Doppler ultrasonography, contrast-enhanced ultrasound, arterial spin labeling MRI, 18F-FDG positron emission tomography, near-infrared spectroscopy (NIRS), functional NIRS, and diffuse correlation spectroscopy. Consensus is lacking regarding the clinical significance of CBF estimations detected by these different modalities. Heterogeneity in the imaging modality used, regional versus global estimations of CBF, time for the scan, and variables impacting brain perfusion and cohort clinical characteristics should be considered when translating the findings described in the literature to routine practice and implementation of therapeutic interventions.Key Points
Keywords: cerebral blood flow; hypoxic–ischemic injury; hypoxic–ischemic encephalopathy; pediatric neurology; neonatal brain